Characterization of an Organic Solvent-Tolerant Protease from Pseudomonas Aeruginosa Strain K - Lee, Poh Geok (2003)
This study involves the isolation and screening of an organic solvent-tolerant producer from eleven Benzene-Toluene-Xylene-Ethylbenzene (BTEX) tolerant bacteria and Polycyclic-Aromatic-Hydrocarbons (PAHs) degraders. The bacteria were initially isolated following qualitative screening on skim milk agar plates and quantitative screening for organic solvent stable protease in liquid media. An organic solvent-tolerant protease producer identified as Pseudomonas aeruginosa strain K was selected for further analysis based on the stability of its protease in 25% (v/v) benzene and toluene. Maximum protease production by Pseudomonas aeruginosa strain K was achieved after 48 h incubation at pH 7.0 and 37°C. Static condition and 4.0% (v/v) bacterial inoculum gave the optimum enzyme yield. Culture media containing sorbitol as the carbon source; casamino acids as the organic nitrogen source and sodium nitrate the inorganic nitrogen source, gave the highest level of protease production. Corn steep liquor, beef extract and ammonium nitrate on the other hand inhibited protease activity. However, the addition of metal ions such as K⁺, Mg²⁺ and Ca²⁺ maximized enzyme synthesis.